Eksplorasi Kebutuhan Konsumen Thrifting Berdasarkan Buyerarchy of Needs : Studi Kasus Pasar Cimol Gedebage (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of thrifting, characterized by the purchase of secondhand clothing, is increasingly popular among urban consumers, particularly at Pasar Cimol Gedebage in Bandung. This study aims to explore and analyze consumer behavior in thrifting using the buyerarchy of needs framework, which categorizes consumer motivations into functional, symbolic, experiential, emotional, social, and epistemic needs. Utilizing a qualitative research method, in-depth interviews were conducted with ten active thrifting consumers in Pasar Cimol Gedebage. The findings reveal that consumer behavior in thrifting is driven not only by functional needs such as affordability and product quality but also by complex psychological and social motivations. These motivations include self-expression, seeking unique shopping experiences, reinforcing social identity, and pride in contributing to sustainable consumption practices. Furthermore, community involvement and consumer knowledge about thrifting significantly shape their decision-making processes. This comprehensive understanding highlights the multifaceted nature of thrifting as a consumption practice that simultaneously integrates economic, emotional, and social dimensions. The study offers valuable insights for thrift business practitioners in developing marketing strategies that holistically address consumer needs by emphasizing emotional engagement and social connections. Ultimately, this research contributes to the broader discourse on sustainable fashion consumption and consumer behavior in emerging markets.